Focal splenic lesions: US findings - Caremani, M. (Springer International Publishing AG, 2013)
Ultrasound (US) imaging of the spleen was considered of little use in the past and was performed only to distinguish between cystic and solid lesions. However, in the last decade due to experience acquired and the introduction of second-generation contrast agents, this technique has been re-evaluated as contrast-enhanced US (CEUS) allows detection and characterization of most focal lesions of the spleen with a high sensitivity and a good specificity. Gray-scale US presents a low specificity in splenic infarctions with a high rate of false negative cases, whereas specificity reaches 100 %, if the examination is performed using US contrast agents. Gray-scale US can provide a correct diagnosis in simple cysts, whereas CEUS is useful when cystic lymphangioma is suspected. In the study of splenic lesions, the most important problem is to differentiate between angioma, hamartoma, lymphoma, and metastasis. CEUS reaches a good specificity in the differentiation of benign from malignant splenic lesions, as hypo-enhancement in the parenchymal phase is predictive of malignancy in 87 % of cases. In conclusion, Gray-scale US and particularly CEUS are at present widely indicated in the study of focal splenic lesions.